Evaluation of antibacterial effect of irrigant solutions (titanium tetra fluoride, green tea, sodium hypochlorite, normal saline) using real-time quantitative - polymerase chain reaction - Heba N Yassin; Zeyneb A Al-Dahan; Mohammed A Hamod (College of Dentistry/ University of Baghdad, 2015)
Background: Removal of bacteria from the pulp system by instrumentation of an infected root canal, will be significantly reduced the number of bacteria, but it is well documented that instrumentation alone can-not clean and kill all bacteria found on the root canal walls. Antibacterial irrigants are needed to kill the remaining microorganisms. The aims of this study was to assess antibacterial effect of titanium tetrafluoride (TiF4) solution and brewing green tea against root canal bacteria and to compare with sodium hypochlorite and normal saline through microbiological and molecular studies. Materials and methods: Microbiological study was carried out to determine the concentration of titanium tetrafluoride and brewing green tea at which they exert antibacterial effect against ten swabs that had been taken from necrotic root canals that were incubated aerobically and anaerobically by paper disk diffusion test, whilemolecular study carried out among Forty children in which the antibacterial effect of titanium tetrafluoride and brewing green tea compared with sodium hypochlorite and normal saline were assessed by real time polymerase chain reaction using SYBR Green. Results: The microbiological study results showed that TiF4 achieved maximum antibacterial effect at concentration 5% against aerobic and anaerobic bacteria while green tea exhibited antibacterial effect when brewed for 20 minutes at concentration 100mg/1ml against staphylococcus aureus, but not active against other microorganisms like Escherichia coli and streptococcus. While results of molecular study illustrated that sodium hypochlorite remained the most effective endodontic irrigant solutions followed by titanium tetrafluoride then green tea while normal saline showed no antibacterial effect. Statistically titanium tetrafluoride, green tea and sodium hypochlorite have significant differences compared to normal saline. Conclusions: This study revealed that, titanium tetra fluoride and brewing green tea can be used as antibacterial irrigant solutions for root canal treatment in children.